Heterakis spumosa Schneider, 1866 (Nematoda: Heterakidae) in Rattus norvegicus (Rodentia: Muridae) in Ica, Peru - Cabrera Ch., Rufino (2001)
In this paper Heterakis spumosa Schneider, 1866 is redescribed. It is a parasitic heterakid nematoda living in the caecum of murid rodent, Rattus norvegícus "gray rat" from district of Parcona, province of Ica, Peru.